Kalangitan kabihasnan designing an astronomical park in the Kaliwa Watershed Forest Reserve Protected Area in Tanay, Rizal - De Matta, Justine Claire E. (College of Architecture, University of the Philippines Diliman, 2025)
Philippine ethnoastronomy is the system of beliefs and practices of ethnolinguistic groups in the Philippines related to astronomical and meteorological phenomena, seen as part of the "upper world" in their three-world cosmology. This knowledge has long guided daily life—shaping farming, fishing, rituals, housebuilding, decisions for good fortune among others. Despite its deep cultural roots, Philippine ethnoastronomy is increasingly at risk of being forgotten due to rapid urbanization, light pollution, and a lack of immersive outdoor environments for cultural and astronomical learning. In response, this study explores the role of landscape architecture in promoting Philippine ethnoastronomy through the creation of a landscape development in Brgy. Cayabu within Kaliwa Watershed Forest Reserve Protected Area in Tanay, Rizal—a site characterized by high elevation, and clear night skies, making it ideal for stargazing and cultural education. The proposed development is envisioned as an ecotourism destination that fosters responsible human interaction with nature while promoting astronomical education and cultural heritage appreciation. Through educational materials and landscape elements, the spaces offer enhanced astronomical observation experience and immersive learning environments. The study involves a site analysis, precedent studies, a focus group discussion (FGD) with the locals, and key informant interviews (KIIs) with experts in astronomy education, serving as a model for ecotourism planning and design within a protected area that fosters learning, environmental stewardship, and cultural preservation through immersive, landscape-based experiences rooted in Philippine ethnoastronomy.